A Role of Activators for Efficient CO2 Affinity on Polyacrylonitrile-Based Porous Carbon Materials - Kamran, Urooj; Choi, Jang Rak; Park, Soo-Jin (Frontiers in Chemistry, 2020)
Herein, we investigated polyacrylonitrile (PAN)-based porous activated carbon sorbents as an efficient candidate for CO2 capture. In this research, an easy and an economical method of chemical activation and carbonization was used to generate activated PAN precursor (PAN-C) adsorbents. The influence of various activators including NaOH, KOH, K2CO3 and KNO3 on the textural features of PAN-C and their CO2 adsorption performance under different temperatures was examined. Among the investigated adsorbents, PANC-NaOH and PANC-KOH exhibited high specific surface areas (2012 and 3072 m2 g−1), with high microporosity (0.82 and 1.15 cm3 g−1) and large amounts of carbon and nitrogen moieties. The PAN-C activated with NaOH and KOH showed maximum CO2 uptakes of 257 and 246 mg g−1 at 273 K and 163 and 155 mg g−1 at 298 K, 1 bar, respectively, which was much higher as compared to the inactivated PAN-C precursor (8.9 mg g−1 at 273 K and 1 bar). The heat of adsorption (Qst) was in the range 10.81–39.26 kJ mol−1, indicating the physisorption nature of the CO2 adsorption process. The PAN-C-based activated adsorbents demonstrated good regeneration ability over repeated adsorption cycles. The current study offers a facile two-step fabrication method to generate efficient activated porous carbon materials from inexpensive and readily available PAN for use as CO2 adsorbents in environmental applications.